Learning Circle Using Gobak Sodor Game Context In Eighth Grade - Harisman Nizar; Dyah Rahmawati (Jurnal Inovasi Matematika, 2024)
This research aims to produce a learning trajectory that can help students understand the concept of circles using the Indonesian Realistic Mathematics Education (PMRI) approach. This research takes the context of the traditional game "gobak sodor" which developed from an informal form to a formal form. The research method used is a research design that involves three stages, namely preparing for the experiment, experimental design, and retrospective analysis. This research was carried out in eighth grade class in one of Junior High School in Palembang involving 34 students. PMRI is the basis for the learning context and activities in this research. Data collection includes taking student work results, interviews, and observations. The results of the research produced a learning trajectory that supports understanding the concept of circles from informal to formal form, which involves one activity of playing "gobak sodor," collecting data through observation and measurement, as well as interpreting data and observations. The results of the learning activities show that the series of activities carried out can help students understand the concept of circles.